The description of syphilis examination results using the immunochromatography method based on gender and age - Yuyun Nailufar; Sri Ramadhani E Akas; Anis Putri Fauziah; Novitawati Novitawati; Margareta Fety Oktavia (Universitas 'Aisyiyah Yogyakarta, 2025)
Syphilis is a sexually transmitted infection (STI) caused by the bacterium Treponema pallidum. Syphilis screening can be performed using the immunochromatography method. Puskesmas (Primary Health Center) Gondokusuman II, Yogyakarta Municipality, provides syphilis screening facilities using the immunochromatography method. This study aims to describe the results of syphilis screening using the immunochromatography method. This study employed descriptive quantitative. The sample of this study was the results of syphilis screening from January 2024 to June 2025 using the Slovin formula, and obtained results from 81 respondents. Based on this study, the results of syphilis screening were predominantly male aged 20-25 years (64.2%), compared to females (35.8%). A high percentage was found in men of productive age or adulthood. This age group has a high curiosity, so it tends to encourage trying new things. The high reactive results based on the results of the examination indicate the potential for infection to spread in the population. The conclusion shows that syphilis examinations in January 2024-June 2025 using the immunochromatography method were dominated by male gender aged 20-25 years or productive age and adult age.